Modification of carbon based cathode electrode in a batch-type microbial fuel cells. (February 2021) - Huang, Song-Jeng; Ubando, Aristotle T.; Wang, Chuan-Yun; Su, Yi-Xun; Culaba, Alvin B.; Lin, Yu-An; Wang, Chin-Tsan
Abstract: Microbial fuel cells (MFCs) provide an efficient way to utilize energy from biomass while it offer advantages such as pollution avoidance, high energy conversion efficiency, and flexibility for a wide range of applications. MFCs have gained much attention and are considered as current research hotspot in bioenergy. To further improve the reaction area, microbial compatibility, and to increase the power generation efficiency in the design and manufacturing of a small-scale MFC, the use of 3D printing technology and the employment of a high-efficiency mixing area are proposed in this work. Carbon cloth is employed as the electrode substrate of the MFC. Moreover, the carbon nanotubes and graphene dispersions are used to modify the carbon electrode plates. The results show that the graphene modified carbon cloth electrode MFC has a maximum power density of 199.24 mW m −2 at a current density of 1.52 A m −2 . While the unmodified carbon cloth electrode MFC has a current density of 0.63 A m −2 . This indicates that the graphene modified carbon cloth electrode MFC achieved a maximum power density of about 232% compared with the unmodified carbon cloth electrode MFC. The lowest internal resistance obtained was 0.66 kΩ when the electron transfer medium was accounted. This indicated a low anode impedance which is desired in MFC systems. Result revealed that the graphene modified carbon cloth electrode is the best electrode material based on the enhanced power density and lowered internal resistance. The results of the work aims to provide insight in the improvement of the MFC electrode modification technology. Highlights: The study aims to improve the power generation efficiency of MFCs. Carbon cloth is employed as an electrode substrate. A designed mixer is introduced to enhance the reaction rate in the MFCs. Results have shown a maximum power density of 0.633 A m −2 . Carbon cloth and graphene are the best choices as plate materials.